A qualitative, grounded theory exploration of the determinants of self-care behavior among Indian patients with a lived experience of chronic heart failure. - Deepak Y Kamath; K B Bhuvana; Luke Joshua Salazar; Kiron Varghese; Anant Kamath; Jyoti Idiculla; Prem Pais; Shruthi Kulkarni; Bradi B Granger; Denis Xavier (PLoS ONE)
Background Prior reports have documented extremely poor adherence to evidence-based medications among South Asian patients with established chronic cardiovascular diseases. Treatment adherence is now considered a part of the 'self-care' process, the determinants of which have not been adequately explored or explained among South Asian patients with chronic heart failure (CHF). Our objective was to qualitatively ascertain the determinants of the self-care process among Indian patients with a lived experience of heart failure. Methods We conducted in-depth interviews (audio-recorded) among 22 purposively sampled patients living with chronic heart failure, diagnosed at least 4 weeks prior to the interview and 17 caregivers (n = 39) in a tertiary care teaching hospital in Southern India. We employed an inductive analytical approach using Charmaz's constructivist grounded theory. Initial line-by-line coding and categorization was followed by memo writing, reflexive analysis after interviewing and analyzing four, eight and twelve patients, and at each stage further theoretical sampling was carried out until we reached thematic saturation. We used NVivo ver. 12 to analyze and organize data. Results The mean age of our patients was 61 years and they represented 5 Indian states and spoke seven languages, distributed across socio-economic strata and literacy levels. We classified self-care determinants into 3 broad, simple categories and defined underlying themes namely, negative determinants (passivity, entrenched beliefs, negative affect, lack of knowledge, financial difficulties, and fatalism), intermediate factors (patient expectations, provider/hospital hopping) and facilitators or positive self-care determinants (intrinsic and extrinsic facilitators). Gender and the cultural background of patients' upbringing appear to shape these determinants, thereby affecting self-care decision making in chronic heart failure. Conclusion We have empirically described a unique set of self-care determinants among Indian chronic heart failure patients, which in turn are shaped by economic and socio-cultural factors. Assessing for and addressing these determinants during clinical interactions through multi-factorial approaches may help improve self-care among Indian CHF patients, thus improving treatment adherence and clinical outcomes.